Banking & capital markets companion - Montagu, Gerald (Exeter : LawMatters, 2003)
The approach and structure of the Banking and Capital Markets Companion is unique. Written with reference to industry standard materials issued by the Loan Market Association,International Swaps and Derivatives Association, and the British Bankers'' Association, it offers ideal support for the Legal Practice Course developed for the City law firms and also acts as a unique one volume reference guide for practitioners.
Overview of Debt Finance,Bank Lending, Loan Transfers, Capital Market Instruments, Collateral and Guarantees, Securitisations, Swaps, UK taxation.
Ηλεκτρονικό βιβλίο
Keywords: Banking law -- Great Britain; Capital market -- Law and legislation -- Great Britain